2013
DOI: 10.1002/rnj.102
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning Home: Comprehensive Case Management for America's Heroes

Abstract: The complex care needs of these returning service members require astute case management in addition to clinical care. This collaboration ensures the best life-long outcomes and will be discussed in detail in this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…All branches of the military have programs dedicated to providing assistance to servicemembers and Veterans with combat-related injuries or illnesses resulting from their involvement in the OIF/OEF/OND conflicts [17]. Helping this cohort of Veterans to adjust and return to full participation in community life roles is also a VA research priority [8,10].…”
Section: Stakeholder Responsementioning
confidence: 99%
“…All branches of the military have programs dedicated to providing assistance to servicemembers and Veterans with combat-related injuries or illnesses resulting from their involvement in the OIF/OEF/OND conflicts [17]. Helping this cohort of Veterans to adjust and return to full participation in community life roles is also a VA research priority [8,10].…”
Section: Stakeholder Responsementioning
confidence: 99%
“…67 Casualties of multiple injuries caused by blast effects may benefit from comprehensive, longitudinal case management to assist in accessing reconstructive and rehabilitative services, as well as identifying more subtle injuries (eg, mTBI) not readily apparent at the initial wounding. 68,69 In addition, for those injured on military service or during certain large-scale terrorist incidents, financial support may be available in different forms to defray living expenses and for caregiver support.…”
Section: Trauma Brain Injurymentioning
confidence: 99%
“…Furthermore, the life of the family is changed forever (Van Houtven et al, 2012). These negative stressors were magnified when the MVC has to cope with polytrauma -a condition which results when the service member or veteran is diagnosed with a TBI, in addition to other multiple injuries Perla, Jackson, Hopkins, Daggett, & Van Horn, 2013;Saban et al, 2016;Stevens et al, 2015;Van Houtven et al, 2012). Researchers also found that one prevalent reason the military caregiver experienced symptoms of depression and stress, was due to the unpredictable responsibilities of caregiving that changed from day to day (Miller et al, 2015;Patel, 2015).…”
Section: Emotional Healthmentioning
confidence: 99%